Conformational Structure, Infrared Spectra and Light-Induced Transformations of Thymol Isolated in Noble Gas Cryomatrices - Jesus, A. J. Lopes (2022)
The conformational space of the natural product thymol (2-isopropyl-5-methylphenol) was investigated using quantum chemical calculations at the B3LYP and MP2 levels, which revealed the existence of four types of conformers differing in the orientation of the isopropyl and hydroxyl groups. Thymol monomers were isolated in noble gas (Ar and Xe) matrices (at 15 K) and characterized by IR spectroscopy. With the support of B3LYP harmonic vibrational calculations, the two most stable trans-OH-conformers, differing in the isopropyl orientation, were identified in the cryomatrices. The two less stable cis-OH conformers were not detected as they shall undergo fast tunneling to the most stable ones. Annealing experiments in a Xe matrix up to 75 K did not lead to any conversion between the two isolated conformers, which is in accordance with the significative energy barrier computed for rotamerization of the bulky isopropyl group (~24 kJ mol−1). Vibrational excitation promoted by broadband or by narrowband irradiation, at the 2ν(OH) frequencies of the isolated conformers, did not lead to any conversion either, which was interpreted in terms of a more efficient energy transfer to the hydroxyl rotamerization (associated with a lower energy barrier and a light H-atom) than to the isopropyl rotamerization coordinate. Broadband UV irradiation experiments (λ > 200 nm) led to a prompt transformation of matrix isolated thymol, with spectroscopic evidence suggesting the formation of isomeric alkyl-substituted cyclohexadienones, Dewar isomers and open-chain conjugated ketenes. The photochemical mechanism interpretation concords with that reported for analogous phenol derivatives.